Perancangan Sistem Informasi Laporan Asset Berbasis Smartphone dengan Metode Waterfall - Budi Dwi Kurniawan; Septi Andryana; Benrahman Benrahman (STMIK Budi Darma, 2020)
Developments in reporting assets at the National University have not been effective. Because the many assets that exist make it difficult for workers to recapitalize the asset report. Such as incoming and outgoing asset reports and asset status status. Therefore, the Smartphone-Based Asset Report Design Information System Designed with the Waterfall Method so that workers can report asset data using smartphones that are more efficient in terms of time and effort. Application trial results for reporting asset data, the application can display report results based on incoming assets, outgoing assets, and asset status accurately. In the search for asset data entered the system can display the results of reports based on transaction id, date of asset entered, and the name of the asset with an accurate level. Then to report the asset data out the system can display the results of the report based on the transaction id, exit, and the name of the asset accurately